2013
DOI: 10.5897/jssem13.0397
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon distribution in alluvial soils according to different flood risk zones

Abstract: This study examines the spatial distribution of organic carbon in alluvial soils subjected to frequent flooding according to different flood risk zones, that is, interval recurrences of 0-20 years (FFz) and 20-100 years (MFz). Sites located outside of flood zones (NFz) were also selected to compare the soil organic carbon (SOC) in different zones. The selected sites are located in floodplains covered by forest dominated by silver maple (Acer saccharinum L.) and green ash (Fraxinus pennsylvanica Marsh.) in sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…The values obtained for the surface horizons (0-20 cm) based on the zones being analyzed are, respectively, p = 0.0008 (FFz and MFz), p = 0.0002 (FFz and NFz), and p = 0.9849 (MFz and NFz) (Figure 4a), while for the statistical values for the entire profile (0-100 cm) are p < 0.001 (FFz and MFz), p < 0.001 (FFz and NFz) and p = 0.99817 (MFz and NFz) (Figure 4b). Comparable values were obtained for the surface horizons covering the soil data from 2003 to 2014 (p < 0.001) [31,37,38]. The TOC for the soils that were analyzed are therefore comparable between the MFz and NFz areas, whereas the soils in the frequent-flood zones stand out through their lower organic carbon content.…”
Section: Total Organic Carbon Contentmentioning
confidence: 64%
See 1 more Smart Citation
“…The values obtained for the surface horizons (0-20 cm) based on the zones being analyzed are, respectively, p = 0.0008 (FFz and MFz), p = 0.0002 (FFz and NFz), and p = 0.9849 (MFz and NFz) (Figure 4a), while for the statistical values for the entire profile (0-100 cm) are p < 0.001 (FFz and MFz), p < 0.001 (FFz and NFz) and p = 0.99817 (MFz and NFz) (Figure 4b). Comparable values were obtained for the surface horizons covering the soil data from 2003 to 2014 (p < 0.001) [31,37,38]. The TOC for the soils that were analyzed are therefore comparable between the MFz and NFz areas, whereas the soils in the frequent-flood zones stand out through their lower organic carbon content.…”
Section: Total Organic Carbon Contentmentioning
confidence: 64%
“…A characterization of the soil litter along with a description of the dominant plant species were noted at each sampling station, as well as measurements of the bulk density of the soil surface horizons (0-20 cm), the microtopography, the presence/absence of groundwater, and the surface drainage based on the criteria outlined in the Canadian System of Soil Classification [35] and the Manual on Soil Sampling and Methods of Analysis [36]. Lastly, other soil data (n = 45) from recent studies (2003 and 2006) on the same Richmond site were incorporated into the database in order to compare all the results [27,37,38]. The position of the sampling points along the transects was determined using a GPS (Garmin 60CSx, Kansas, MI, USA), after which the data were exported into mapping software (ArcGIS ® 10.2, ESRI, Redlands, CA, USA).…”
Section: Selection Of Sites and Collection Of Soil Samplesmentioning
confidence: 99%
“…For example, between 1960 and 2010, over 60 flood events were recorded in south-central Québec catchments, with close to 50% occurring in the spring [58]. Because of these new hydrologic conditions resulting from increased flooding, it can be easily assumed that they will deeply alter floodplain soils, including an alteration of soil-forming processes and soil depletion (in terms of C and N, for instance), induced by the loss of ground litter resulting from successive floods [26,27,58]. Furthermore, successive floods that progressively modify the fluvial environment could cause major alterations to riparian forests, namely in relation to the regeneration capacity of the tree stratum and the maintenance of current forest stands [61].…”
Section: Flood Eventsmentioning
confidence: 99%
“…Thicker (>5 cm) organo-mineral (Ah) horizons are found that are enriched with humified particles, along with illuvial horizons (Bm, Bfj, or Bf horizons) that indicate active soil-forming processes, including the accumulation of Al and Fe sesquioxides. Flood frequency thus has a direct impact on soil development, especially for alluvial soils subjected to successive flooding with profiles that can be qualified as "rejuvenation profiles" [26,27]. …”
Section: Littermentioning
confidence: 99%
See 1 more Smart Citation